Case studies in interpersonal communication processes and problems - Braithwaite, Dawn O.; Wood, Julia T. (Wadsworth/Thomson Learning, 2000)
The many narrative cases in this book offer dramatic, real-life snapshots of interpersonal theory in action. Written by established communication scholars and reflecting carefully conducted research, each case helps you apply abstract principles to specific situations, people, and relationships. As you read these cases, you'll also learn to appreciate how multiple communication dynamics work together to shape what happens in human interactions - for example, how a case focusing on self-disclosure also gives you insights into such issues as timing, context, and style of communication. And as you identify patterns revealed in the cases, you'll develop the ability to detect these patterns in your own interactions and ultimately make more informed choices about which patterns to foster and avoid in your interpersonal relationships.